Novel Functions of the Neurodegenerative-Related Gene Tau in Cancer - Gargini, Ricardo; Segura-Collar, Berta; Sánchez-Gómez, Pilar (Frontiers in Aging Neuroscience, 2019)
The analysis of global and comparative genomics between different diseases allows us to understand the key biological processes that explain the etiology of these pathologies. We have used this type of approach to evaluate the expression of several neurodegeneration-related genes on the development of tumors, particularly brain tumors of glial origin (gliomas), which are an aggressive and incurable type of cancer. We have observed that genes involved in Amyotrophic lateral sclerosis (ALS), as well as in Alzheimer's and Parkinson's diseases, correlate with better prognosis of gliomas. Within these genes, high Tau/MAPT expression shows the strongest correlation with several indicators of prolonged survival on glioma patients. Tau protein regulates microtubule stability and dynamics in neurons, although there have been reports of its expression in glial cells and also in gliomas. However, little is known about the regulation of Tau/MAPT transcription in tumors. Moreover, our in silico analysis indicates that this gene is also expressed in a variety of tumors, showing a general correlation with survival, although its function in cancer has not yet been addressed. Another remarkable aspect of Tau is its involvement in resistance to taxanes in various tumors types such as breast, ovarian and gastric carcinomas. This is due to the fact that taxanes have the same tubulin-binding site as Tau. In the present work we review the main knowledge about Tau function and expression in tumors, with a special focus on brain cancer. We will also speculate with the therapeutic implications of these findings.